Acute myeloid leukaemia: challenges and real world data from India. (9th April 2015) - Philip, Chepsy; George, Biju; Ganapule, Abhijeet; Korula, Anu; Jain, Punit; Alex, Ansu Abu; Lakshmi, Kavitha M.; Sitaram, Usha; Abubacker, Fouzia N.; Abraham, Aby; Viswabandya, Auro; Srivastava, Vivi M.; et al.
Summary The management of acute myeloid leukaemia (AML) in India remains a challenge. In a two‐year prospective study at our centre there were 380 newly diagnosed AML (excluding acute promyelocytic leukaemia, AML‐M3) patients. The median age of newly diagnosed patients was 40 years (range: 1–79; 12·3% were ≤ 15 years, 16·3% were ≥ 60 years old) and there were 244 (64·2%) males. The median duration of symptoms prior to first presentation at our hospital was 4 weeks (range: 1–52). The median distance from home to hospital was 580 km (range: 6–3200 km). 109 (29%) opted for standard of care and were admitted for induction chemotherapy. Of the 271 that did not take treatment the major reason was lack of financial resources in 219 (81%). There were 27 (24·7%) inductions deaths and of these, 12 (44·5%) were due to multidrug‐resistant gram‐negative bacilli and 12 (44·5%) showed evidence of a fungal infection. The overall survival at 1 year was 70·4% ± 10·7%, 55·6% ± 6·8% and 42·4% ± 15·6% in patients aged ≤15 years, 15 ‐ 60 years and ≥60 years, respectively. In conclusion, the biggest constraint is the cost of treatment and the absence of a health security net to treat all patients with this diagnosis.